The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12909-020-02235-w
|View full text |Cite
|
Sign up to set email alerts
|

Has teaching about intellectual disability healthcare in Australian medical schools improved? A 20-year comparison of curricula audits

Abstract: Background People with intellectual disability (ID) have multiple and complex health needs, more frequent healthcare episodes, and experience poorer health outcomes. Research conducted two decades ago showed that medical professionals were lacking in the knowledge and skills required to address the complex needs of this patient group. The aim of the current study was to determine whether Australian undergraduate medical schools that offer ID health education content had changed the amount and nature of such te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…First, train health professionals in recognizing and addressing the health needs of people with ID. Australian research has shown that health care professionals are underequipped to deal with the health needs of people with ID, owing to a lack of appropriate training . Specific education and training for health professionals at all stages, from medical school to specialist training, on providing care for people with ID, can lead to earlier identification and better management of conditions that are amenable to health care.…”
mentioning
confidence: 99%
“…First, train health professionals in recognizing and addressing the health needs of people with ID. Australian research has shown that health care professionals are underequipped to deal with the health needs of people with ID, owing to a lack of appropriate training . Specific education and training for health professionals at all stages, from medical school to specialist training, on providing care for people with ID, can lead to earlier identification and better management of conditions that are amenable to health care.…”
mentioning
confidence: 99%
“…Despite the increasing knowledge on the needs for specific skills and knowledge in medical care providers [ 11 , 36 ], authors of recent review articles agree that medical care for people with IDD still lacks adequate support [ 9 11 , 37 , 38 ]. This lack can possibly be addressed by systematically increasing the attention/priority for the special medical care needs of people with IDD in medical curricula and education [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, audits of intellectual disability content in medical and nursing curricula across Australian universities found intellectual disability content and teaching methods vary greatly between universities. These audits found only 10% of nursing schools, and 15% of medical schools offered substantial intellectual disability health content, and few universities offered direct clinical contact with people with intellectual disability (Trollor et al, 2020; Trollor, Eagleson, et al, 2016; Trollor, Eagleson, Turner, Salomon, et al, 2018; Trollor, Eagleson, Turner, Tracy, et al, 2018; Trollor, Ruffell, et al, 2016). Research also shows health professionals lack the capacity and confidence to meet the health needs of people with intellectual disability (Weise & Trollor, 2018).…”
Section: Australia's Healthcare System: Responding To the Needs Of Pe...mentioning
confidence: 99%